ACANTHAMOEBA SP.S-11 PHAGOCYTOTIC ACTIVITY ON MYCOBACTERIUM LEPRAE IN DIFFERENT NUTRIENT CONDITIONS - Paling, Sepling; Wahyuni, Ratna; Ni’matuzahroh, DEA; Winarni, Dwi; Iswahyudi, M. KES; Astari, Linda; Adriaty, Dinar; Agusni, Indropo; Izumi, Shinzo (African Journal of Infectious Diseases (AJID), 2018)
Background: Mycobacterium leprae (M. leprae) is a pathogenic bacterium that causes leprosy. The presence of M. leprae in the environment is supported by microorganisms that act as the new host for M. leprae. Acanthamoeba’s potential to be a host of M. leprae in the environment. Acanthamoeba sp. is Free Living Amoeba (FLA) that classified as holozoic, saprophytic, and saprozoic. The existence of nutrients in the environment influence Acanthamoeba ability to phagocytosis or pinocytosis. This study is aimed to determine Acanthamoeba sp.S-11 phagocytic activity to Mycobacterium leprae (M. leprae) which cultured in non-nutrient media and riched-nutrient media.Materials and Methods: This research conducted by culturing Acanthamoeba sp.S-11 and M. leprae on different nutrient media conditions. M. leprae intracellular DNA were isolated and amplified by M. leprae specific primers through Real Time PCR (Q-PCR).Result: The results showed that Acanthamoeba co-cultured on non-nutrient media were more active to phagocyte M. leprae than on rich-nutrient media.Conclusion: The use of non-nutrient media is recommended to optimize Acanthamoeba sp. phagocytic activity to M. leprae.Keywords: Acanthamoeba sp., Mycbacterium leprae, Nutrient, Phagocytosis, Real Time PCRIntroductionMycobacterium leprae (M. leprae) is a pathogenic